Physical and nutritional properties of extruded products based on whole grain with the addition of wild legumes (Vicia lutea subsp. lutea var. hirta and Vicia sativa subsp. sativa) - Pastor Cavada, Elena (2013)
Flour blends based on whole corn and rice with two added wild legumes at 15% level of cereal replacement were extruded to produce whole grain snacks. Extrusion temperature was 175 °C, and the moisture content was adjusted to 14%. The extruded products were evaluated for their physical, chemical and nutritional properties. Results showed that the addition of legumes produces a decrease in expansion in rice-containing samples and an increase in solubility in corn-containing samples. With only 15% of legume added to cereal, a significant increase in protein content and quality was obtained. An increase in fibre, polyphenol, iron and zinc content was also obtained. Protein digestibility was in the range of 81.8– 85.3%. Mineral availability ranged from 6.4 to 16.3% for iron and 10–16.3% for zinc. The performance of each mixture during extrusion and the physical properties of the extruded products were considered to be similar to those expected for snack-type products and described in the literature.